Per la critica della violenza fotografica: Le ricerche visuali di Susan Sontag (Balthazar, 2025)
Susan Sontag’s interest in visual research, documented by numerous essays, is closely linked to the central role that the author has recognized in the photographic gaze, in understanding a series of cognitive and social processes in modern capitalist societies. Her approach has highlighted, over a period ranging from the early Seventies to the early 2000s, a series of effects of construction and deconstruction in the formation of common sense, linking them to the settlement of forms of social intimacy with the photographic medium. Sontag’s long-standing interest in the history of photography, and in the evolution of consumer practices related to this medium, testifies to the political engine of her research: recognizing the principles of construction of social reality between representation, power of fiction and information overload, developing a critical understanding of capitalist society through the traffic of images that innervates it.